Comparative Efficacy and Safety of Selective Serotonin Reuptake Inhibitors and Serotonin‐Norepinephrine Reuptake Inhibitors in Older Adults: A Network Meta‐Analysis. Issue 5 (6th May 2015) - Thorlund, Kristian; Druyts, Eric; Wu, Ping; Balijepalli, Chakrapani; Keohane, Denis; Mills, Edward
<x xml:space="preserve">Abstract</x> Objectives To establish the comparative efficacy and safety of selective serotonin reuptake inhibitors and serotonin‐norepinephrine reuptake inhibitors in older adults using the network meta‐analysis approach. Design Systematic review and network meta‐analysis. Participants Individuals aged 60 and older. Measurements Data on partial response (defined as at least 50% reduction in depression score from baseline) and safety (dizziness, vertigo, syncope, falls, loss of consciousness) were extracted. A Bayesian network meta‐analysis was performed on the efficacy and safety outcomes, and relative risks (RRs) with 95% credible intervals (CrIs) were produced. Results Fifteen randomized controlled trials were eligible for inclusion in the analysis. Citalopram, escitalopram, paroxetine, duloxetine, venlafaxine, fluoxetine, and sertraline were represented. Reporting on partial response and dizziness was sufficient to conduct a network meta‐analysis. Reporting on other outcomes was sparse. For partial response, sertraline (RR = 1.28), paroxetine (RR = 1.48), and duloxetine (RR = 1.62) were significantly better than placebo. The remaining interventions yielded RRs lower than 1.20. For dizziness, duloxetine (RR = 3.18) and venlafaxine (RR = 2.94) were statistically significantly worse than placebo. Compared with placebo, sertraline had the lowest RR for dizziness (1.14) and fluoxetine the second lowest (1.31). Citalopram, escitalopram, and paroxetine all had RRs between 1.4 and 1.7. Conclusion There was clear evidence of the effectiveness of sertraline, paroxetine, and duloxetine. There also appears to be a hierarchy of safety associated with the different antidepressants, although there appears to be a dearth of reporting of safety outcomes.